People of destiny : Gandhi - Torgersen, Don Arthur, 1934- (Chicago, Childrens Press, 1968)
Includes Index
Includes Index
Bibliography: p. 90-93.
Basic Ed. Students
Keywords: Gandhi, -- Mahatma, -- 1869-1948.